(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Animal husbandry in Indonesia is one way to meet food needs in Indonesia. The people’s farm school program has now become a national program known as the people’s livestock center. . One of the results of cattle raising is to increase family income. The research aims to produce an analysis of the level of participation of members in activities, analysis of the level of income of members, and analyze the relationship of the level of participation with the level of income of SPR members Muara Tigo Manunggal. The study uses survey methods with quantitative data in the form of questionnaires which are supported by qualitative data in-depth interviews with DPPT members. The number of respondents in the study was 34 people by taking 20 percent of the population. The results showed the level of member participation in SPR activities was still relatively low, the level of farmers’ income was moderate, and there was a relationship between the level of participation and income level. Keywords: animal husbandry, food needs, income levels, participation, sekolah peternakan rakyat Â ABSTRAK Peternakan di Indonesia merupakan salah satu cara untuk pemenuhan kebutuhan pangan di Indonesia. Program sekolah peternakan rakyat sekarang telah menjadi program nasional yang dikenal dengan sentra peternakan rakyat. . Hasil dari ternak sapi salah satunya adalah untuk meningkatkan pendapatan keluarga. Penelitian bertujuan untuk menghasilkan analisis tingkat partisipasi anggota dalam kegiatan, analisis tingkat pendapatan anggota, serta menganalisis hubungan tingkat partisipasi dengan tingkat pendapatan anggota SPR Muara Tigo Manunggal. Penelitian menggunakan metode survei dengan data kuantitatif berupa kuesioner yang didukung oleh data kualitatif wawancara mendalam dengan anggota DPPT. Jumlah responden dalam penelitian adalah 34 orang dengan cara mengambil 20 persen dari populasi. Hasil penelitian menunjukkan tingkat partisipasi anggota dalam kegiatan SPR masih tergolong rendah, tingkat pendapatan peternak tergolong sedang, dan terdapat hubungan antara tingkat partisipasi dengan tingkat pendapatan. Kata Kunci: kebutuhan pangan, partisipasi, peternakan, sekolah peternakan rakyat, tingkat pendapatan